2017
DOI: 10.1007/s11060-017-2386-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A1 is upregulated in human glioblastoma

Abstract: Serum amyloid A1 (SAA1) is a sensitive acute phase reactant primarily produced by the liver in response to acute inflammation. We have recently shown that SAA affects proliferation, migration, and invasion of glioblastoma cell lines, which suggest its participation in the malignant process. Consistently, levels of SAA have been used as a non-invasive biomarker for the prognosis of many cancers. In this study, we aimed to investigate SAA serum levels and expression of SAA genes in human astrocytomas tissues. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Knebel et al (2017) found that SAA1 was both expressed and secreted by human glioblastoma cells. SAA production was associated with tumor associated macrophages of the M2 type.…”
Section: Saa and Cancermentioning
confidence: 99%
“…Knebel et al (2017) found that SAA1 was both expressed and secreted by human glioblastoma cells. SAA production was associated with tumor associated macrophages of the M2 type.…”
Section: Saa and Cancermentioning
confidence: 99%
“…The correlation of SAA1 with human glioblastomas was proposed in a recent study (Knebel et al ., ). The study revealed that SAA1 was upregulated 10 to 60 times in patients with glioblastomas compared with patients with non‐neoplastic and other grades of astrocytoma.…”
Section: Discussionmentioning
confidence: 97%
“…Knebel et al . () also found that serum levels of SAA1 were associated with the grades of gliomas but did not affect the clinical outcomes of patients with GBM. By contrast, we found that the gene expression levels of SAA1 in brain tumors were associated with glioma malignancy and patient mortality at threshold 25 (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations